Achieving ADA/ISPAD clinical guideline goals is associated with higher insulin sensitivity and cardiopulmonary fitness in adolescents with type 1 diabetes: Results from RESistance to InSulin in Type 1 ANd Type 2 diabetes (RESISTANT) and Effects of MEtformin on CardiovasculaR Function in AdoLescents with Type 1 Diabetes (EMERALD) Studies. Issue 3 (30th October 2017) - Bjornstad, Petter; Cree‐Green, Melanie; Baumgartner, Amy; Coe, Gregory; Reyes, Yesenia Garcia; Schäfer, Michal; Pyle, Laura; Regensteiner, Judith G; Reusch, Jane EB; Nadeau, Kristen J
Abstract : Objective: Most youth with type 1 diabetes do not meet the American Diabetes Association (ADA) and International Society for Pediatric and Adolescent Diabetes (ISPAD) targets for hemoglobin A1c (HbA1c), blood pressure (BP), lipids, and body mass index (BMI). We hypothesized that ISPAD/ADA goal achievement would be associated with better insulin sensitivity (IS) and cardiopulmonary fitness. Methods: IS was quantified as glucose infusion rate (GIR) from a hyperinsulinemic‐euglycemic clamp in youth with type 1 diabetes from the RESistance to InSulin in Type 1 ANd Type 2 diabetes (RESISTANT) ( n = 86) and Effects of MEtformin on CardiovasculaR Function in AdoLescents with Type 1 Diabetes (EMERALD) ( n = 41) cohorts ( n = 127; age 15.7 ± 2.2 years, 52% girls). Cardiopulmonary fitness was measured as peak oxygen consumption (VO2 peak/kg) during upright (RESISTANT) or supine (EMERALD) cycle ergometry and were stratified by cycle type. Goal achievement was defined as HbA1c < 7.5%, BP < 90th percentile, LDL‐cholesterol < 100 mg/dL, HDL‐cholesterol > 35 mg/dL, triglycerides < 150 mg/dL and BMI < 85th percentile. Participants were stratified into 3 groups: achieving 0‐3 goals ( n = 52), 4 goals ( n = 48), and 5‐6 goals ( n = 27). Differences between groups were examined with generalized linear models. Results: IS was lower in youth who met 0‐3 goals (5.2 ± 3.4 mg/kg/min) vs those who met 4 goals (7.4 ± 4.1 mg/kg/min, P = .04) and those who met 5‐6 goals (8.5 ± 4.3 mg/kg/min, P = .003), and remained significant after adjustments for sex and diabetes duration. Upright VO2 peak was lower in youth who met 0‐3 goals (25.8 ± 4.6 mL/kg/min) vs those who met 4 goals (33.0 ± 7.8 mL/kg/min, P = .01) and those who met 5‐6 goals (33.2 ± 4.4 mL/kg/min, P = .004). Similar and significant relationships were observed in EMERALD participants for supine VO2 peak. Conclusions: ADA/ISPAD goal achievement was associated with greater IS and cardiopulmonary fitness.